Horizontal right axillary minithoracotomy: aesthetic and effective option for atrial and ventricular septal defect repair in infants and toddlers - Silva,Luciana da Fonseca da (2014)
Introduction: Congenital heart defects treatment shows progressive reduction in morbidity and mortality, however, the scar, resulting from ventricular (VSD) and atrial septal defect (ASD) repair, may cause discomfort. Right axillary minithoracotomy approach, by avoiding the breast growth region, is an option for correction of these defects that may provide better aesthetic results at low cost. Since October 2011, we have been using this technique for repairing VSD and ASD defects as well as associated defects. Objectives: To evaluate the efficacy of this method in children undergoing correction of VSD and ASD, to compare perioperative clinical outcomes with those repaired by median sternotomy, and to evaluate the aesthetic result. Methods: Perioperative clinical data of 25 patients submitted to axillary thoracotomy were compared with data from a paired group of 25 patients with similar heart defects repaired by median sternotomy, from October 2011 to August 2012. Results: Axillary approach was possible even in infants. There was no mortality and the main perioperative variables were similar in both groups, except for lower use of blood products in the axillary group (6/25) vs. control (13/25), with statistical difference (P =0.04). The VSD size varied from 7 to 15 mm in axillary group. Cannulation of the aorta and vena cavae was performed through the main incision, whose size ranged from 3 to 5 cm in the axillary group, with excellent aesthetic results. Conclusion: The axillary thoracotomy was effective, allowing for a heart defect repair similar to the median sternotomy, with more satisfactory aesthetic results and reduced blood transfusion, and it can be safely used in infants.